Modelling of the drying of eggplants in thin-layers - Akpinar, EK; Bicer, Y (Oxford Univ Press, 2005)
In this paper, the thin-layer drying behaviour of eggplant slices (6 mm thick layers) in a convective-type cyclone dryer is reported. Thin-layer drying experiments were conducted at drying air temperatures of 55, 65 and 75 degreesC and dry air velocities of 1 and 1.5 ms(-1). Data on sample mass, temperature and velocity of the dry air were recorded continuously during each test. In order to estimate and select a suitable form of the drying curve, eight different semi-theoretical and/or empirical models were fitted to the experimental data and comparisons made of their coefficients of determination as predicted by non-linear regression analysis. The Page model best described the drying curve of eggplant, with a correlation coefficient, r = 0.9999.
Keywords: drying models; mathematical modelling; moisture ratio; non-linear regression